Identifying patients with psychosocial problems in general practice: A scoping review - Schwenker, Rosemarie; Deutsch, Tobias; Unverzagt, Susanne; Frese, Thomas (Frontiers in Medicine, 2023)
Objective We conducted a scoping review with the aim of comprehensively investigating what tools or methods have been examined in general practice research that capture a wide range of psychosocial problems (PSPs) and serve to identify patients and highlight their characteristics. Methods We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews and the Joanna Briggs Institute Reviewer’s Manual on scoping reviews. A systematic search was conducted in four electronic databases (Medline [Ovid], Web of Science Core Collection, PsycInfo, Cochrane Library) for quantitative and qualitative studies in English, Spanish, French, and German with no time limit. The protocol was registered with Open Science Framework and published in BMJ Open. Results Of the 839 articles identified, 66 met the criteria for study eligibility, from which 61 instruments were identified. The publications were from 18 different countries, with most studies employing an observational design and including mostly adult patients. Among all instruments, 22 were reported as validated, which we present in this paper. Overall, quality criteria were reported differently, with studies generally providing little detail. Most of the instruments were used as paper and pencil questionnaires. We found considerable heterogeneity in the theoretical conceptualisation, definition, and measurement of PSPs, ranging from psychiatric case findings to specific social problems. Discussion and conclusion This review presents a number of tools and methods that have been studied and used in general practice research. Adapted and tailored to local circumstances, practice populations, and needs, they could be useful for identifying patients with PSPs in daily GP practice; however, this requires further research. Given the heterogeneity of studies and instruments, future research efforts should include both a more structured evaluation of instruments and the incorporation of consensus methods to move forward from instrument research to actual use in daily practice.